2018
DOI: 10.3168/jds.2017-12948
|View full text |Cite
|
Sign up to set email alerts
|

Using models to establish the financially optimum strategy for Irish dairy farms

Abstract: Determining the effect of a change in management on farm with differing characteristics is a significant challenge in the evaluation of dairy systems due to the interacting components of complex biological systems. In Ireland, milk production is increasing substantially following the abolition of the European Union milk quota regime in 2015. There are 2 main ways to increase the milk production on farm (within a fixed land base): either increase the number of animals (thus increasing the stocking rate) or incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…During the period of milk quota restrictions, in order for farmers to maximize farm profit, they had to maximize profit per unit of product, typically achieved by producing milk in a least cost per unit of product format, generally from a predominantly pasture-based diet. In terms of individual farm management, the response rates of milk production to increased concentrate feeding and other purchased feeds are greatly influenced by several variables including pasture quality, pasture allowance, stocking rate, and dairy cow genetics (Roche et al, 2006;Ruelle et al, 2018). When pasture quality is poor or limiting DMI of the cow (or both), the response to concentrate will be increased in comparison to a cow being fed greater quality or quantity (or both) of pasture, thus affecting the levels of substitution (reduction in pasture intake when supplementary feeds are consumed by the cow; Bargo et al, 2003), combined with a maintenance requirement on a proportion of the consumed energy (Roche et al, 2009).…”
Section: Supplementary Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…During the period of milk quota restrictions, in order for farmers to maximize farm profit, they had to maximize profit per unit of product, typically achieved by producing milk in a least cost per unit of product format, generally from a predominantly pasture-based diet. In terms of individual farm management, the response rates of milk production to increased concentrate feeding and other purchased feeds are greatly influenced by several variables including pasture quality, pasture allowance, stocking rate, and dairy cow genetics (Roche et al, 2006;Ruelle et al, 2018). When pasture quality is poor or limiting DMI of the cow (or both), the response to concentrate will be increased in comparison to a cow being fed greater quality or quantity (or both) of pasture, thus affecting the levels of substitution (reduction in pasture intake when supplementary feeds are consumed by the cow; Bargo et al, 2003), combined with a maintenance requirement on a proportion of the consumed energy (Roche et al, 2009).…”
Section: Supplementary Feedmentioning
confidence: 99%
“…Although in a high milk price year it could be assumed increased supplementary feed usage would increase farm profitability, it has been reported that the key determinant here is the difference between milk price and feed costs, and not the price of milk or feed costs in a given year (Hansen et al, 2005). In reality it can be more difficult to manage higher input systems as there is a greater complexity of the overall system through more decision rules required on an ongoing basis, which requires higher levels of skill to manage (Ruelle et al, 2018).…”
Section: Supplementary Feedmentioning
confidence: 99%
“…In support, Ramsbottom et al (2015) reported that the cost of the marginal milk produced from imported feeds was greater than the milk price received in systems utilising >500 kg DM/cow purchased feeds. Recent results from farm systems experiments in Ireland (Ruelle et al, 2018) and New Zealand Roche J. R., unpublished data) concur; the cost of marginal milk produced from inexpensive purchased feeds was greater than a moderate to good milk price, despite very good marginal milk production responses to the purchased feed.…”
Section: Figurementioning
confidence: 85%
“…The herd profile and technological differences among the systems are possible explanations for this discrepancy. Furthermore, it has also been previously reported that variability of milk price has greatest influence on profitability (Ruelle et al, 2018). Hence, in an era of increased levels of milk price volatility (Hemme et al, 2014), producers require to maximize production efficiencies and, in particular, business resilience (Shadbolt, 2012).…”
Section: Discussionmentioning
confidence: 99%